PSEUDOMONAS AERUGINOSA IN CHRONIC SUPPURATIVE OTITIS MEDIA: SENSITIVITY SPECTRUM AGAINST VARIOUS ANTIBIOTICS IN KARACHI - Mansoor, Tahira; Musani, Mohammed Ayub; Khalid, Gulnaz; Kamal, Mustafa (Journal of Ayub Medical College Abbottabad, 2009)
Background: Chronic suppurative otitis media (CSOM) is a prevailing and notorious infection in developing countries causing serious local damage and threatening complications. Early and effective treatment based on the knowledge of causing micro organisms and their sensitivity results in good clinical recovery and prevents from damage and complications. Pseudomonas aeruginosa is most common pathogen causing CSOM in Pakistan. The objective of this study is to identify incidence of Pseudomonas aeruginosa involved in CSOM and sensitivity against commonly prescribed antibiotics. Methods: A total of 263 patients with unilateral or bilateral chronic suppurative otitis media (CSOM) were enrolled in the study at Department of ENT, Karachi Medical and Dental College & Abbasi Shaheed Hospital, Karachi, Pakistan from December 2004 to May 2006. Sterile cotton swabs were used to collect pus from discharging ears and plated on Blood agar and MacConkey agar for 24 to 48 hours. Antibiotics susceptibility was tested by Minimum inhibitory concentrations (MIC) method using Mueller-Hinton agar. Results: Overall microbiology of 267 samples from 263 patients was studied including 4 of bilateral discharge. Polymicrobial growth was present in 8 samples. A total of 275 bacterial isolates were studied. Pseudomonas aeruginosa (40%) and Staphylococcus aureus (30.9%) were the most common bacterial agents found in CSOM. MIC was done for Pseudomonas aeruginosa only as it was the commonest pathogen found in CSOM. Sensitivity pattern of Pseudomonas aeruginosa showed that amikacin was active against 96% of isolates followed by ceftazidime 89%, ciprofloxacin 85%, gentamicin 81%, imipenem 76%, aztreonam 42% and ceftriaxone 21%. Conclusions: Pseudomonas aeruginosa was the most common bacteria isolated from chronic discharging ears followed by Staphylococcus aureus. Amikacin was found to be the most suitable drug followed by ceftazidime and ciprofloxacin for Pseudomonas aeruginosa. The resistance against ceftriaxone and aztreonam was found to be very high. Keywords: Chronic suppurative otitis media, Antibiotic resistance, Pseudomonas aeruginosa